FINE STRUCTURAL LOCALIZATION OF ACETYLCHOLINESTERASE IN ELECTROPLAQUE OF THE ELECTRIC EEL - Bloom, Floyd E. (The Rockefeller University Press, 1966)
The electroplaques composing the electric organ of the eel, Electrophorus electricus, have been utilized for the dual purpose of demonstrating the subcellular sites of acetylcholinesterase activity and as a model for comparison of the several cytochemical methods available. Fresh tissue and tissue fixed by immersion in formalin, hydroxyadipaldehyde, or glutaraldehyde was reacted with the Cu-thiocholine method, the Cu-ferrocyanide thiocholine method, or the thiolacetic acid (TAA) method using Pb, Ag, or Au as capture reagents. Controls were obtained by omission of substrate, or by addition to complete media of varying concentrations of different cholinesterase inhibitors. Reactions were run at 0–5°C at a pH range of 5.0–7.1 for 0.25 to 120 min. Regardless of the capture metal, the localization obtained with TAA as substrate was identical with that observed with acetylthiocholine, the majority of precipitate being deposited on or near the external innervated surface of the plaque and within the tubulovesicular organelles opening onto the innervated surface. Both of the thiocholine methods and the Pb-TAA method showed reaction product in synaptic vesicles of the nerve endings innervating the plaque which was uninhibitable by 10(-4) M physostigmine. All methods also showed some inhibitor-sensitive deposition of reaction product in the mucoid material forming the immediate extracellular environment of the innervated surface.